2016
DOI: 10.1002/adma.201600839
|View full text |Cite
|
Sign up to set email alerts
|

Cloning Nacre's 3D Interlocking Skeleton in Engineering Composites to Achieve Exceptional Mechanical Properties

Abstract: Ceramic/polymer composite equipped with 3D interlocking skeleton (3D IL) is developed through a simple freeze-casting method, exhibiting exceptionally light weight, high strength, toughness, and shock resistance. Long-range crack energy dissipation enabled by 3D interlocking structure is considered as the primary reinforcing mechanism for such superior properties. The smart composite design strategy should hold a place in developing future structural engineering materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 45 publications
0
85
0
Order By: Relevance
“…This leads to the enhanced alignment and restricts the flowability of hydrophilic 2D flakes. Some of the flakes could be swallowed by the growing ice dendrites . The architecture consisting of highly oriented MXene layers and interconnected bridges was further confirmed by the XRD patterns comparison of Ti 3 C 2 T x aerogel before and after rolling (Figure S4, Supporting Information).…”
mentioning
confidence: 58%
“…This leads to the enhanced alignment and restricts the flowability of hydrophilic 2D flakes. Some of the flakes could be swallowed by the growing ice dendrites . The architecture consisting of highly oriented MXene layers and interconnected bridges was further confirmed by the XRD patterns comparison of Ti 3 C 2 T x aerogel before and after rolling (Figure S4, Supporting Information).…”
mentioning
confidence: 58%
“…Montmorillonite (MMT) is a commonly used filler due to its large surface area and high aspect ratio of its laminar structure . The recent inorganic ceramic‐based material research focuses strongly on the enhancing the mechanical properties by utilizing nature inspired 3D structure . For example, Liang et al showed that high strength, high toughness, and shape memory MMT/ALG composites could be achieved by chemical modification.…”
Section: Introductionmentioning
confidence: 76%
“…Survey of nacre‐like ceramic/polymer matrix bulk composites . A,B) Specific elastic modulus and specific strength compared to (A) other nacre‐like composites and (B) traditional engineering materials.…”
mentioning
confidence: 99%